Dialysis Catheters and Their Common Complications: An Update - Satyaki Banerjee (The Scientific World Journal)
Tunneled dialysis catheters (TDCs) are associated with the highest rate of complications, morbidity, and mortality when compared to arteriovenous fistulas or grafts, and this relates to higher costs in their management. Over time, catheters are prone to higher rates of infection, thrombosis, and central venous stenosis, and, thereby, catheter dysfunction. Lower blood flow rates are a consequence of the dysfuncion. Despite efforts to reduce incident and prevalent rates of catheter use for dialysis by the National Kidney Foundation and Fistula First Initiative, they remain a common modality of hemodialysis. The management of common TDC-related complications is discussed, in addition to ways to reduce and prevent morbidity associated with their use.